Neuregulin-1β increases glucose uptake and promotes GLUT4 translocation in palmitate-treated C2C12 myotubes by activating PI3K/AKT signaling pathway - Yu, Meirong; Wu, Shuang; Gong, Chao; Chen, Lianhua (Frontiers in Pharmacology, 2023)
Insulin resistance (IR) is a feature of type 2 diabetes (T2DM) accompanied by reduced glucose uptake and glucose transporter 4 (GLUT4) translocation by skeletal muscle. Neuregulin-1β (NRG-1β) is essential for myogenesis and the regulation of skeletal muscle metabolism. NRG-1β increases insulin sensitivity, promotes glucose uptake and glucose translocation in normal skeletal muscle. Here, we explored whether NRG-1β increased glucose uptake and GLUT4 translocation in palmitate (PA)-treated C2C12 myotubes. After C2C12 myoblasts differentiated into myotubes, we used PA to induce cellular IR. Cells were incubated with or without NRG-1β and glucose uptake was determined using the 2-NBDG assay. The expression level of glucose transporter 4 (GLUT4) was measured via immunofluorescence and Western blotting. MK2206, an inhibitor of AKT, was employed to reveal the important role played by AKT signaling in PA-treated C2C12 myotubes. We then established an animal model with T2DM and evaluated the effects of NRG-1β on body weight and the blood glucose level. The GLUT4 level in the gastrocnemius of T2DM mice was also measured. NRG-1β not only increased glucose uptake by PA-treated myotubes but also promoted GLUT4 translocation to the plasma membrane. The effect of NRG-1β on PA-treated C2C12 myotubes was associated with AKT activation. In T2DM mice, NRG-1β not only improved diabetes-induced weight loss and diabetes-induced hyperglycemia, but also promoted GLUT4 translocation in the gastrocnemius. In summary, NRG-1β increased glucose uptake and promoted translocation of GLUT4 to the plasma membrane in PA-treated C2C12 myotubes by activating the PI3K/AKT signaling pathway.